On the Existence of Solutions for the Critical Fractional Laplacian Equation in ℝN - Zifei Shen; Fashun Gao (Abstract and Applied Analysis)
We study existence of solutions for the fractional Laplacian equation -Δsu+Vxu=u2*s-2u+fx, u in ℝN, u∈Hs(RN), with critical exponent 2*s=2N/(N-2s), N>2s, s∈0, 1, where Vx≥0 has a potential well and f:ℝN×ℝ→ℝ is a lower order perturbation of the critical power u2*s-2u. By employing the variational method, we prove the existence of nontrivial solutions for the equation.